PENGARUH PENGGUNAAN MEDIA GAMBAR BERSERI TERHADAP KEMAMPUAN MENULIS TEKS RECOUNT DALAM BAHASA INGGRIS SISWA KELAS X SMAS DDI KENDARI - La Ode Fendi Donga; Ader Laepe (Universitas Halu Oleo, 2021)
Students' abilities are the ability to write paragraphs, write according to grammar rules, sentence structure, choose the right words and the ability to use punctuation marks correctly. This research uses experimental methods. The number of population is in accordance with the number of samples, namely 40 class X people consisting of 2 classes. The sample class consists of the experimental class and the control class. Data were collected using tests. Then the data were analyzed quantitatively and qualitatively using statistical analysis, namely the t-test and two-way test at the 0.05 significance level. The results showed that there was a significant difference between students' writing skills based on serial pictures and without using serial pictures. Through data analysis it was found that the t-test value was greater (5.57) than the t-table (2.09) for the 0.05 percent significance level. The results of the study support the hypothesis which states that tenth grade students can write recount text well based on serial images.